Автоматическое управление внешним магнитным полем технических объектов - Розов, В.Ю.; Ассуиров, Д.А. (Технічна електродинаміка, 2011)
The principles of automatic control of external magnetic field of technical objects which are based on the control of scalar potential of magnetic field on the surface of objects with the help of surface-distributed system of contours with control currents are considered. The methods of their realization which permit to ensure the practical problem solutions of automatic control of external magnetic field of technical objects including their surface are suggested